Knowledge and Attitude of Medan Selayang Citizens Toward Kidney Diseases in Children - Viria Milenia; Rosmayanti Syafriani Siregar; Tasrif Hamdi; Ririe Fachrina Malisie (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
Background. Renal disease define as groups of heterogenous disease that affect the function and structure of kidney. Children with end-stage renal disease (ESRD) have 30 times mortality rate than children without ESRD. Early signs and symptoms should be recognized and risk factors should be identified early so kidney disease could be prevented and slow the progress towards worse condition. Prevention can be done by parents and society by hindering or eliminating risk factor from children that could cause kidney disease.  Therefore, society’s knowledge and attitude towards children’s kidney disease need to be carried out, especially parents,which are child’s first point contact with medical staff.   Objective. To describe the level of knowledge about symptoms, risk factors, treatment and complications of kidney diseases and precautionary attitude of Medan Selayang citizens towards kidney diseases in children. Methods. The research was a descriptive observational study with cross sectional approach. The sampling method used was non-probability sampling with convenient method. Total sample needed in this research is 100 people who were Medan Selayang citizens that brought children to Puskesmas PB II Selayang.This study used questionnaire as research tool. Results : From 100 respondents, 67% knew that children can get kidney disease and 81% agree that some kidney diseases can be prevented. Conclusion. The knowledge of Medan Selayang’s citizens was still lack especially regarding symptoms, risk factors, and complications. The attitude of the citizens was good.